Voluntary Imitation in Alzheimer’s Disease Patients - Bisio, Ambra; Casteran, Matthieu; Ballay, Yves; Manckoundia, Patrick; Mourey, France; Pozzo, Thierry (Frontiers in Aging Neuroscience, 2016)
Although Alzheimer's disease (AD) primarily manifests as cognitive deficits, the implicit sensorimotor processes that underlie social interactions, such as automatic imitation, seem to be preserved in mild and moderate stages of the disease, as is the ability to communicate with other persons. Nevertheless, when AD patients face more challenging tasks, which do not rely on automatic processes but on explicit voluntary mechanisms and require the patient to pay attention to external events, the cognitive deficits resulting from the disease might negatively affect patients’ behaviour. The aim of the present study was to investigate whether voluntary motor imitation, i.e. a volitional mechanism that involves observing another person’s action and translating this perception into one’s own action, was affected in patients with Alzheimer’s disease. Further, we tested whether this ability was modulated by the nature of the observed stimulus by comparing the ability to reproduce the kinematic features of a human demonstrator with that of a computerized-stimulus. AD patients showed an intact ability to reproduce the velocity of the observed movements, particularly when the stimulus was a human agent. This result suggests that high-level cognitive processes involved in voluntary imitation might be preserved in mild and moderate stages of AD and that voluntary imitation abilities might benefit from the implicit interpersonal communication established between the patient and the human demonstrator.